KOMPOSISI SAPLING PADA KAWASAN PENYANGGA DI PERKEBUNAN KELAPA SAWIT KILIRAN JAO KECAMATAN KAMANG BARU KABUPATEN SIJUNJUNG - Mardian, Gusmayeni - (Pendidikan Biologi, 2014)
Sapling is the young trees have high more than 1,5 m and diameters < 10 cm. knowledge of the saplingis very important because it describes the regeneration of trees in the future. Research aboutcomposition of sapling at buffer zone in palm plantation Kiliran Jao Kecamatan Kamang BaruKabupaten Sijunjung. have been carried out from Juni until August 2014 by using the transect withquadrate plot. The results showed the composition of seedling at buffer zone was 30 species 17families and 110 individuals. The highest individual of sapling at buffer zone was Euphorbiaceae (38individual). The highest relative diversity was Mallotus subpeltatus (20,909%). Species have thehighest relative frequency was Mallotus subpeltatus dan Semecarpus sp. (9,231%). Euphorbiaceae iscategorized as dominant family while the family Anacardiaceae, Annonaceae and Leeaceae can becategorized as a co-dominant.